A critical ethnographic evaluation of pediatric haematology/oncology physicians and burn-out. (17th February 2020) - Mahon, Paula
Abstract: This qualitative study aims to ascertain what it is that affects pediatric hematology/oncology physicians professional and personal attitudes within their work environment. This research is based in one pediatric oncology unit in western Canada using a critical ethnographic research approach. Critical ethnography was the methodology used to conduct this study. Critical Ethnography (CE) is an interpretative research methodology that allows the researcher to evaluate the cultural aspects of a group, or an organization 'within their setting'; to understand and expose the meaning of the relationships in that environment; without meaning being imposed on them externally. 11 physicians (N = 11) participated in this study, this represents approximately 80% of the physician population in this unit. Semi-structured interviews were conducted which lasted an average of 36 minutes per interview. Physicians described their relationships with colleagues, patients and families as both rewarding but also producing symptoms of burn-out. The majority agreed that they enjoy their job because of the constantly evolving research and scientific updates in oncology research. There is a paradox of conflicting satisfiers and dissatisfiers mainly pertaining to patient, parent, physician relationships. Consideration to offering sabbatical leave should be assessed.